Introduction to the Special Issue: New Diplomatic Histories of Turkey. Issue 2 (4th March 2023) - Kuru, Deniz; Papuççular, Hazal
ABSTRACT: This article provides an introduction to the special issue on 'New Diplomatic Histories of Turkey'. Utilizing approaches that follow the rich pathways offered by the increasingly relevant new diplomatic history, we aim to go beyond traditional diplomatic history studies on Turkey, which usually focus on inter-state relations that mostly remain at the bilateral levels. In this regard, this introduction first analyses the recent turn taking place in diplomatic history. By portraying in detail the recent scholarly efforts to enhance the field, it becomes possible to pinpoint the multiple directions in which Turkey-pertinent diplomatic–historical studies could move ahead in novel ways. Upon this premise, second, we summarize the content of the special issue by emphasizing how the present articles connect studies on the diplomacy of Turkey to approaches enriched by new diplomatic history. In this regard, the studies in this special issue cover a wide range of topics, from transnationalism to public diplomacy. The last part deals with possible ways through which to widen the scope of Turkey's diplomatic histories.